The Influence of Work Discipline and Work Environment on Employee Performance at Setia Mitra Hospital, South Jakarta - Syawaludin Syawaludin (Peneliti.net, 2022)
This study aims to determine how the influence of work discipline and work environment on employee performance at the Setia Mitra Hospital, South Jakarta, to find out how the influence of work discipline on employee performance at the Setia Mitra Hospital, South Jakarta, to find out how the influence of the work environment on employee performance at the Setia Mitra Hospital, South Jakarta. The method used in this research is quantitative method, namely through the approach, data collection and analysis using statistics. A population of 208 employees with the determination of the sample using the Slovin formula with a level of difficulty of 10% obtained 68 samples. The data used through observation techniques, questionnaires and literature. The analysis method used in this research is validity test, reliability test, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, multiple linear regression test, determination test and significant test (t test and f test). The results showed that partially work discipline has a positive effect on employee performance, this can be seen from the t test with a tcount of 4.002> 2.382, partially the work environment has a positive effect on employee performance, this can be seen from the t test with a tcount of 4.163> 2.382 and Simultaneously work discipline and work environment have a positive and significant effect on employee performance, this can be seen from the results of the F test with Fcount 10.630 and Ftable 2.38 (10.630> 2.38), multiple linear regression obtained by the equation Y = 21,393 + 0.228 X1 + 0.286 X2 with the coefficient of determination adjusted R square is 0.223 or 22.3%..